2008
DOI: 10.1055/s-2008-1039939
|View full text |Cite
|
Sign up to set email alerts
|

10 Jahre zementfreie Implantation von Hüfttotalendoprothesen unter Verwendung des Zweymüller-Schaftes

Abstract: A retrospective study of the first consecutive 111 cementless Zweymüller Stems has been performed. 56 cases have been followed clinically and radiologically with an interval of 10-11 years. The average harris hip score was 90.7 pts, the cumulative success rate of the stem was 97.96% after 10-11 years. The frequency of bony reactions around the stem and their changes during the course of time could be followed in 40 implants with a complete radiologic documentation at 5 and 10 years postoperative. Hypertrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…The rate of patients with thigh pain was low in our cohort, comparing well with the lower rates of thigh pain reported in the literature for uncemented stems, which, although not always reported in studies, varies from 0% to 17% [1, 25, 35, 39]. Naumann et al [31] reported 29% of patients had thigh pain during the first months after surgery and 5.6% had pain remaining afterward, for the first generation of the Zweymüller stem.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The rate of patients with thigh pain was low in our cohort, comparing well with the lower rates of thigh pain reported in the literature for uncemented stems, which, although not always reported in studies, varies from 0% to 17% [1, 25, 35, 39]. Naumann et al [31] reported 29% of patients had thigh pain during the first months after surgery and 5.6% had pain remaining afterward, for the first generation of the Zweymüller stem.…”
Section: Discussionsupporting
confidence: 85%
“…However, an incidence of thigh pain of 5.7% to 17% was reported with the early designs [25, 35, 39] contrasting with the absence of pain reported by Flecher et al [13, 14] with the anatomic custom stems. Therefore an anatomic cementless stem was designed, based on a computerized three-dimensional (3-D) analysis of a 300 CT scan database, which allowed defining an average metaphyseal femoral shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the first generation of the Zweymüller system, four publications fulfilled the inclusion criteria [1][2][3][4]. Two studies [3,4] dealt with the whole system (cup and stem); the stem [1] and the cup [2] alone were treated in one study each.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [3,4] dealt with the whole system (cup and stem); the stem [1] and the cup [2] alone were treated in one study each.…”
Section: Resultsmentioning
confidence: 99%